CEREBELLAR ATAXIA PRESENTING WITH LATE-ONSET AUTOIMMUNE DIABETES MELLITUS: A CASE REPORT - Ing, Shan Kai; Ling, Tiing Yun; Ng, Benjamin Han Sim; Lau, Eunice Yi Chwen (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Glutamic acid decarboxylase antibodies (GAD-Ab) are the predominant autoantibodies present in most adult-onset autoimmune diabetes cases. Furthermore, high levels of GAD-Ab have been associated with neurological syndromes such as stiff person syndrome, cerebellar ataxia, epilepsy, limbic encephalitis and other overlapping syndromes. We present a patient who exhibited symptoms of cerebellar ataxia and new-onset diabetes mellitus CASE A 38-year-old female with a medical history of endometrial polyps presented with a one-month history of progressive gait instability and vertigo resulting in difficulty ambulating. She had also experienced polydipsia and polyuria for two weeks. Neurological examination revealed staccato speech and gait ataxia with bilateral dysmetria and dysdiadochokinesia. No nystagmus or diplopia was observed. Power and tone were normal, with hyperreflexia in the left bicep and patella. Her glucose level at presentation was 28.9 mmol/L with no ketoacidosis. Cranial MRI was unremarkable, and CSF analysis showed lymphocytic pleocytosis with elevated protein levels. CSF screening for infection, paraneoplastic antibodies and oligoclonal bands yielded negative results. Her CSF GAD-Ab was positive, and her serum GAD-Ab was markedly elevated (280 IU/L), as were her anti-islet cell antibodies (87.5 IU/mL). Her HbA1c was 10.9%, with evidence of proteinuria but no diabetic retinopathy. She was managed with intravenous (IV) immunoglobulin and methylprednisolone followed by oral steroids, with subsequent improvement in her ataxic gait. Her diabetes was managed with basal-bolus insulin. CONCLUSION Autoimmune cerebellar ataxia is a rare condition that can be associated with high levels of GAD-Ab and, frequently, autoimmune diabetes. As this condition may result in chronic disabling neurological impairment, prompt diagnosis to facilitate treatment is imperative.